Packaging and Branding Strategy to Increase the Competitiveness of Bolu Jadul Business in Bulungan Village, Jepara - Isna Istiqomah; Hefied Adibatul Husna; Khofifatul Lubaba; Ahmad Saefudin; Hudi Hudi (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
This community development focuses on increasing the competitiveness of partners in the home industry-based processed cake business. The subject of devotion leads to the development of product quality with various innovations. The goal is including the lack of innovation in the marketing process, cake production is still fluctuating and tends to decline, and the appearance of product packaging is very simple. The Team uses Participatory Action Research (PAR) as an approach. In a participatory manner, the service team encourages partners to take transformative actions through various activities. As a result, in the production sector, partners have succeeded in marketing Jadul Bolu cake products with online and offline systems. In the field of business management, partners are trained to make packaging or labeling of Bolu Jadul cakes. In the field of marketing, partners utilize internet technology through the use of social media, Instagram.